Skin microbiome variation with cancer progression in human cutaneous squamous cell carcinoma - Voigt, Anita Yvonne; Emiola, Akintunde; Johnson, Jethro S.; Fleming, Elizabeth S.; Nguyen, Hoan; Zhou, Wei; Tsai, Kenneth Y.; Müller-Christmann, Christine; Oh, Julia (The journal of investigative dermatology, 2022)
The skin microbiome plays a critical role in skin homeostasis and disorders. UVR is the major cause of nonmelanoma skin cancer, but other risk factors, including immune suppression, chronic inflammation, and antibiotic usage, suggest the microbiome as an additional, unexplored risk factor and potential disease biomarker. The overarching goal was to study the skin microbiome in squamous cell carcinoma (SCC) and premalignant actinic keratosis compared with that in healthy skin to identify skin cancer‒associated changes in the skin microbiome. We performed a high-resolution analysis of shotgun metagenomes of actinic keratosis and SCC in healthy skin, revealing the microbial community shifts specific to actinic keratosis and SCC. Most prominently, the relative abundance of pathobiont Staphylococcus aureus was increased at the expense of commensal Cutibacterium acnes in SCC compared with that in healthy skin, and enrichment of functional pathways in SCC reflected this shift. Notably, C. acnes associated with lesional versus healthy skin differed at the strain level, suggesting the specific functional changes associated with its depletion in SCC. Our study revealed a transitional microbial dysbiosis from healthy skin to actinic keratosis to SCC, supporting further investigation of the skin microbiome for use as a biomarker and providing hypotheses for studies investigating how these microbes might influence skin cancer progression.